Sanitary, phytosanitary and technical barriers to trade in the economic partnership agreements between the European Union and the ACP countries - Denise Prévost (International Centre for Trade and Sustainable Development (ICTSD), 2010)
The paper investigates how abusive use of EPA provisions for sanitary, phytosanitary and technical barriers in EPAs could be an obstacle to market access. The study also promotes experience sharing among different ACP regions in terms of drawing up negotiating positions. The issues covered include: The EPAs' disciplines on traditional barriers to market access, including tariffs and quotas; Provisions addressing non-traditional barriers to trade in the WTO agreements and the various EPAs; Technical regulations, standards and conformity assessments procedures; Sanitary and phytosanitary measures; The relationship between the EPAs' rules on non-traditional barriers to trade and those in the WTO agreements ...
Keywords: 330